2-Litre polyethylene glycol-citrate-simethicone plus bisacodyl versus 4-litre polyethylene glycol as preparation for colonoscopy in chronic constipation. Issue 10 (October 2015) - Parente, Fabrizio; Vailati, Cristian; Bargiggia, Stefano; Manes, Gianpiero; Fontana, Paola; Masci, Enzo; Arena, Monica; Spinzi, Giancarlo; Baccarin, Alessandra; Mazzoleni, Giorgia; Testoni, Pier Alberto
Abstract Background Chronic constipation is a risk factor of inadequate bowel preparation for colonoscopy; however, no large clinical trials have been performed in this subgroup of patients. Aims To compare bowel cleansing efficacy, tolerability and acceptability of 2-L polyethylene-glycol-citrate-simethicone (PEG-CS) plus 2-day bisacodyl (reinforced regimen) vs. 4-L PEG in patients with chronic constipation undergoing colonoscopy. Methods Randomized, observer-blind, parallel group study. Adult outpatients undergoing colonoscopy were randomly allocated to 2-L PEG-CS/bisacodyl or 4-L PEG, taken as split regimens before colonoscopy. Quality of bowel preparation was assessed by the Ottawa Bowel Cleansing Scale (OBCS). The amount of foam/bubble interfering with colonic visualization was also measured. Results 400 patients were enrolled. There was no significant difference in successful cleansing (OBCS score ≤6): 80.2% in the 2-L PEG-CS/bisacodyl vs. 81.4% in the 4-L PEG group. Significantly more patients taking 2L PEG-CS/bisacodyl showed no or minimal foam/bubbles in all colonic segments (80% vs. 63%; p < 0.001). 2-L PEG-CS/bisacodyl was significantly more acceptable for ease of administration (p < 0.001), willingness to repeat (p < 0.001) and showed better compliance (p = 0.002). Conclusion Split 2-L PEG-CS plus bisacodyl was not superior to split 4-L PEG for colonoscopy bowel cleansing in patients with chronic constipation; however, it performed better than the standard regimen in terms of colonic mucosa visualization, patient acceptance and compliance.